KONSEP PENDIDIKAN INKLUSIF DALAM HADIST TARBAWI TELAAH: ATAS PERLAKUAN NABI TERHADAP ANAK, PEREMPUAN, DAN KAUM DIFABEL - Ryan Radjendra; Sulastri; Gani, Ainul; Cahaya Kesuma, Guntur; Amirudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the principles of inclusive education within tarbawi hadiths through the educational practices of Prophet Muhammad SAW toward children, women, and persons with disabilities. Inclusive education is understood as an educational approach that ensures equal access, justice, and respect for human dignity without discrimination. Using a qualitative descriptive method with a library research design, this study analyzes hadith texts and relevant Islamic education literature to identify inclusive values embedded in prophetic educational practices. The findings indicate that the Prophet’s educational approach was fundamentally inclusive and humanistic. In the education of children, the Prophet emphasized compassion (rahmah) and emotional closeness as the foundation of character building. In terms of women’s education, hadiths demonstrate explicit recognition of women’s rights to access knowledge and participate actively in learning processes. Meanwhile, in educating persons with disabilities, the Prophet applied proportional justice by providing appropriate accommodations without diminishing their social roles or moral status. These findings affirm that inclusive education is not a modern construct imposed upon Islamic thought, but rather an integral part of prophetic pedagogy. The study concludes that the values of compassion, equality, and respect for diversity found in tarbawi hadiths remain highly relevant for developing inclusive Islamic education systems that respond to the needs of diverse learners in contemporary contexts.